2017
DOI: 10.1159/000477293
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment at 3 Years in Neonates Born by Vaginal Delivery versus Cesarean Section at <26 Weeks of Gestation: Retrospective Analysis of a Nationwide Registry in Japan

Abstract: Background: A high proportion of extremely preterm (EPT) infants are born by cesarean section (CS). However, whether the mode of delivery is related to long-term neurodevelopment in these infants is unclear. Objectives: This study aimed to determine whether the mode of delivery is associated with mortality and long-term outcomes in EPT infants. Methods: We analyzed data of the Neonatal Research Network in Japan (NRNJ), a population-based, nationwide registry. Inclusion criteria were neonates who were born betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…Our results are consistent with other studies regarding full-term, preterm, breech presentation children or twins, and these studies also found no significant difference in developmental and behavioral outcomes between cesarean and vaginal-delivered groups (Asztalos et al, 2016; Bahl et al, 2007; Dekeunink et al, 2016; Haque et al, 2008; Joseph et al, 2015; Kimura et al, 2017; Robson et al, 2015; Spinillo et al, 1992; Zhu et al, 2014). However, previous studies have found some negative outcomes due to cesarean delivery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with other studies regarding full-term, preterm, breech presentation children or twins, and these studies also found no significant difference in developmental and behavioral outcomes between cesarean and vaginal-delivered groups (Asztalos et al, 2016; Bahl et al, 2007; Dekeunink et al, 2016; Haque et al, 2008; Joseph et al, 2015; Kimura et al, 2017; Robson et al, 2015; Spinillo et al, 1992; Zhu et al, 2014). However, previous studies have found some negative outcomes due to cesarean delivery.…”
Section: Discussionsupporting
confidence: 93%
“…However, the existing research evidence is not consistent relating to the effects of cesarean section on child health outcomes. For example, some studies have shown that the cesarean section was not associated with a reduction in risk of death or neurodevelopmental delay in children (Asztalos et al, 2016; Bahl et al, 2007; Dekeunink et al, 2016; Haque et al, 2008; Joseph et al, 2015; Kimura et al, 2017; Robson et al, 2015; Spinillo et al, 1992; Whyte et al, 2004; Zhu et al, 2014), while others argued that cesarean section significantly reduced the risk of children neurodevelopmental delay in a specific case (Molkenboer et al, 2006). Some other studies showed that cesarean section may have a negative impact on the baby’s respiratory system and immune system (Lee et al, 2014; Shearer, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in neurodevelopmental outcomes in periviable infants has improved since the early 21st century; however, studies assessing neurologic outcomes as they relate to delivery mode have been mixed. 11 Obi can et al 27 and Kimura et al 28 found no difference in long-term neurologic outcomes, as determined by Bayley II scores, between delivery modes for infants born before 26 weeks' gestation. However, these studies were limited by an underpowered sample size to detect small, but Original Research potentially clinically significant differences and a high rate of missing neurodevelopmental data, respectivley.…”
Section: Research Implicationsmentioning
confidence: 96%
“…However, these studies were limited by an underpowered sample size to detect small, but Original Research potentially clinically significant differences and a high rate of missing neurodevelopmental data, respectivley. 27,28 In contrast, K€ all en et al 26 found that a vaginal breech delivery was associated with developmental cognitive delays in infants born before 27 weeks' gestation. The true reason for the association between improved survival rates and delivery via cesarean delivery between 22 0/7 to 23 6/7 weeks gestational age and if there are improved long-term neurologic outcomes remains unclear, and further studies are warranted to elucidate this.…”
Section: Research Implicationsmentioning
confidence: 96%
“…Many pregnant women choose this practice of delivery in their hometown, and their infants are raised in the NICU away from the place where they will grow up afterward. Thus, the NRNJ studies have had a high percentage (43–63%) of drop-outs [2224]. We did not choose earlier ages for evaluation because too short a duration of follow-up may have compromised the accuracy of estimating the prevalence of children with epilepsy.…”
Section: Discussionmentioning
confidence: 99%